"I'm making a positive change in my life": A mixed method evaluation of a well‐being tertiary education unit. Issue 2 (13th May 2022) - Piggott, Ben; Chivers, Paola; Bulsara, Caroline; Conlon, Jenny; Grigg, Kaine; Harris, Sarah Ann; Lambert, Michelle; Millar, Lynne; Pollard, Christina M.
Abstract: Issue Addressed: Mental health disorders (MHDs) are prevalent amongst university students with detrimental impacts on individual students, universities and the wider community. There is an urgent need for proactive and preventative strategies to address the mental health crisis in the university population. This study evaluated the efficacy of a 13‐week unit developed to directly educate university students about ways to improve and maintain well‐being. Methods: Fifty‐eight university students from five disciplines participated in a 13‐week elective undergraduate unit "Well‐Being Fundamentals for Success" as part of their degree. The Act Belong Commit mental health promotion campaign framework formed the basis of teaching materials. Outcome well‐being measures were self‐assessed at weeks 1, 6 and 12 using four scales: (1) Warwick‐Edinburgh Mental Well‐being Scale (WEMWBS); (2) Perceived Stress Scale (PSS); (3) Brief Resilience Scale (BRS) and (4) Mindful Attention Awareness Scale (MAAS). Post‐unit group interviews (n = 11) were analysed for key themes. Results: Linear mixed models demonstrated a significant improvement in BRS over the semester; well‐being (WEMBS) and mindful attention (MAAS) did increase but not significantly. There was a significant increase in stress (PSS) over the semester. Key themes that emerged from the group interviews were that (1) University life contributes to well‐being; (2) University life contributes to stress; (3) The well‐being unit helped students see and do things differently; (4) An overall endorsement of the unit. Conclusion: University students' resilience increased over the semester following participation in a curriculum focused on well‐being which featured a combination of theoretical content and experiential workshops. So what? Incorporating mental well‐being curriculum into tertiary education is proactive preventive health strategy which may assist with the increasing prevalence of MHD in Australia.